Electrolyte Imbalance As A Key Contributor To Unexplained Pain In Chronic Kidney Disease Patients Undergoing Haemodialysis: An Observational Study - Sreeja PA; Sreya Kosanam; Abirami Shanthakumar; N. Harikrishnan; Dawn VJ (Revista Electronica de Veterinaria, 2024)
Background: Chronic kidney disease (CKD) patients on hemodialysis often experience unexplained pain, potentially exacerbated by electrolyte imbalances. This study aims to investigate the prevalence of pain in this population and its association with mineral levels, particularly phosphorus and calcium. Methods: An observational study was conducted involving 62 CKD patients undergoing hemodialysis. Demographic data, pain prevalence, location, severity, and frequency were assessed using structured questionnaires. Blood urea, phosphorus, calcium, potassium, and creatinine levels were measured pre- and post-dialysis. Statistical analyses, including chi-square tests, were employed to explore relationships between mineral levels and pain characteristics. Results: Of the participants, 66.13% reported experiencing pain, predominantly localized in the legs (40.32%) and arms (19.35%). The majority rated their pain as mild (58.53%) and reported it as occasional (87.80%). Notably, 53.23% exhibited elevated phosphorus levels, while 91.93% had low calcium levels. Chi-square analysis demonstrated significant associations between mineral imbalances and pain experiences (χ² = 167.51, p < 0.00001), highlighting a potential correlation between elevated phosphorus and low calcium levels with reported pain. Discussion: This study underscores the high prevalence of pain among hemodialysis patients and the critical need for comprehensive pain assessment and management. The observed associations between electrolyte imbalances and pain suggest that careful monitoring of phosphorus and calcium levels may be essential for improving patient outcomes. Conclusion: Electrolyte imbalances, particularly elevated phosphorus, and low calcium, significantly contribute to pain in CKD patients undergoing hemodialysis. Enhanced monitoring and targeted interventions to address these imbalances are crucial for improving pain management and overall quality of life in this vulnerable population.